WAYS TO ANALYZE AND INCREASE THE EFFICIENCY OF THE ECONOMY OF THE INDUSTRIAL SECTOR IN UZBEKISTAN - Toraboyeva Kimiyokhon Orazbekovna (American Journals, 2025)
This article provides a detailed overview of the indicators reflecting the economic efficiency of the industrial sector and the factors influencing it. An analysis of the role of the industrial sector in the national economy, its economic potential, and efficiency indicators has been conducted. Additionally, scientifically grounded proposals have been developed to further enhance the economic efficiency of the industrial sector.
Keywords: Industry, industrial sector, industrial products, economic efficiency, economic potential, economic growth.